PENYELARASAN RENCANA BIAYA DENGAN SUMBER PENDANAAN ORGANISASI PENDIDIKAN ISLAM - Rohaniyah, Aisyah; Mardiyah, Mardiyah (STKIP Pesisir Selatan, 2025)
This article aims to identify the components of education costs and their funding sources. Strategic planning in Islamic education plays an important role in managing budgets and funding sources to ensure the effectiveness and sustainability of education. Strategic management includes cost planning, resource allocation and budget alignment with various funding sources such as government funds, community contributions, zakat, infaq and waqf. This article uses a descriptive method with a literature study approach to analyze budgeting and financial management strategies in Islamic education. The results show that aligning cost plans with appropriate funding sources can improve financial efficiency, prevent budget deficits and increase transparency. In addition, optimizing education funds through innovative strategies such as financial digitalization and transparent audit systems can support the sustainability of Islamic education programs. With proper planning, Islamic education can develop better, increase competitiveness, and produce a generation of academic and moral excellence.